Evaluasi Program Supervisi Akademik Berbasis Refleksi dalam Meningkatkan Efektivitas Manajemen Kelas Guru SMP Negeri 1 Kemangkon - Anang Kurnia Wahab; Muh. Hanif; Ali Muhdi; Sri Winarsih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aimed to evaluate the implementation of a reflective academic supervision program in improving teachers' classroom management effectiveness at SMP Negeri 1 Kemangkon. A qualitative evaluative approach employing the Context, Input, Process, Product (CIPP) evaluation model was adopted to assess program relevance, resource readiness, implementation quality, and program outcomes. Data were collected through in-depth interviews, classroom observations, and document analysis involving the principal, vice principal, teachers, and students selected using purposive sampling. Data were analyzed using the Miles and Huberman interactive model, while credibility was ensured through source triangulation, technique triangulation, and member checking. The findings indicate that, in the context dimension, reflective academic supervision corresponded closely with teachers' needs in addressing classroom management challenges. In the input dimension, the school demonstrated adequate readiness through structured supervision programs, competent school leadership, appropriate supervision instruments, and strong institutional support. Regarding the process dimension, evidence-based classroom observation, reflective dialogue, constructive feedback, and teacher reflection formed an integrated cycle of professional learning that promoted instructional improvement. In the product dimension, the program enhanced teachers' classroom management skills, increased student engagement, created a more conducive classroom climate, and strengthened teachers' professional confidence. This study proposes the Reflective Classroom Improvement Model (RCIM), which conceptualizes teacher reflection as the mediating mechanism linking academic supervision to classroom management effectiveness. The model extends the application of the CIPP framework beyond program evaluation by explaining the mechanism through which reflective supervision fosters sustainable professional growth and instructional improvement.